Managing outpatient consultations: from referral to discharge. Issue 4 (9th March 2017) - Mitchell, Rachael; Jacob, Hannah; Morrissey, Benita; Macaulay, Chloe; Gomez, Kumudini; Fertleman, Caroline
Abstract : Although a great deal of paediatric consultations are not urgent, doctors in training spend so much time providing service for acute conditions that they spend little time focusing on outpatient work before they become a consultant. Engaging clinicians in the managerial aspects of providing clinical care is a key to improving outcomes, and this article addresses these aspects of the outpatient consultation from referral to discharge. We aim to provide doctors in training with a tool to use during their training and their first few years as a consultant, to think about how outpatient work is organised and how it can be improved to maximise patient experience. The non-urgent consultation varies across the world; this article is aimed to be relevant to an international audience.